Planificación De Entrenamiento Deportivo Orientada Al Desarrollo De Los Fundamentos Técnicos Del Baloncesto Caso: Estudiantes Categoría Intermedia Distrito Chambo – Riobamba - Cando Brito, Karolina Janeth; Gutierrez Cayo, Henry Rodolfo; Ponce Bravo, Hernán Leopoldo; Ponce Franco, Christian Hernán; Moreno, Orlando David Mazón (European Scientific Journal, ESJ, 2017)
The present research work responds to the planning of sports training oriented towards the development of the technical fundamentals of basketball. Specifically, the study was applied in the Chambo-Riobamba district of Chimborazo, Ecuador. The study was conducted based on a previous study on the analysis of the technical fundamentals of basketball. It details the need to develop a plan that is oriented towards the students of the intermediate category of the district. Through student survey, this study aims to avert the problem that demonstrates the absence of an oriented planning that is reflected in the low sport performance in this sport. The methodology used was through direct observation. The surveys were conducted for students, coaches, and field research. As a result, it is possible to define and apply daily training plans to determine how the universe of this study was responding to the exercise plan. The plan is made up of 29 sessions divided into 1 macrocycle, 7 mesocycles, and 25 microcycles. In conclusion, we ascertain that the sports training plan is a necessary tool for the physical, psychological, and skill preparation of the athletes in the practice of the technical fundamentals of the basketball. In addition, it demonstrated better results in the district and provincial competences of the Educational Units belonging to the objective of this study.